The Impact of Alternative Access Modes on Urban Public Transport Network Design - van Nes, Rob (European Journal of Transport and Infrastructure Research, 2001)
Public transport network design determines the quality for travellers as well as operational costs. Network design is therefore crucial for the cost effectiveness of urban public transport. In urban public transport network design it is commonly assumed that all travellers walk to the stops. This might be true for short access distances, but if stop and line spacing increase other modes such as bicycles might become interesting as an alternative access mode. An analytical model is presented that determines optimal network characteristics, i.e. stop spacing, line spacing, and frequency, and that explicitly accounts for alternative access modes. The objective used is maximising social welfare. Results show that, if cycling is considered as an alternative access mode, all three network characteristics mentioned above should be increased, offering benefits for the traveller, the operator as well as the society. However, if there is a large sub-population of travellers who are not able to use the alternative mode, or if there are barriers for using an alternative mode to access the urban public transport system, it is better to assume that walking is the only access mode available. In the case of cycling as an access mode there are possibilities for positive benefits, at least in countries such as Denmark or the Netherlands. It is expected that for other access modes, such as peoplemovers and demand responsive public transport systems, the barriers are too high to have an impact on urban public transport network design.